2021
DOI: 10.3390/jcm10163547
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in Inflammatory and Obstructive Salivary Gland Diseases: Own Experiences and a Review of the Literature

Abstract: Background: Ultrasound is established as a diagnostic tool in salivary glands for obstructive diseases such as sialolithiasis and tumors. Concerning inflammatory diseases and in non-sialolithiasis-caused obstruction, much fewer data are available. In recent years, technical development has allowed a better assessment of the gland parenchyma, and knowledge about intraductal pathologies has increased considerably, which has provided new insights and a new interpretation of ultrasound findings. Objectives: To pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 142 publications
(202 reference statements)
0
25
0
Order By: Relevance
“…ASL may also be useful for evaluating systemic inflammatory disease that manifests as sialadenitis. Immunoglobulin G4 (IgG4)-related disease is a systemic fibro-inflammatory disease, which can affect the salivary glands in more than 30–40% of patients, submandibular glands more often than parotid glands, and bilateral salivary glands more often than unilateral salivary gland [ 58 ]. Other than salivary gland lesions, the most commonly involved organ is reportedly the lacrimal gland [ 59 ] ( Figure 5 ).…”
Section: Clinical Applications Of 3d Tse Pcasl In the Head And Neckmentioning
confidence: 99%
“…ASL may also be useful for evaluating systemic inflammatory disease that manifests as sialadenitis. Immunoglobulin G4 (IgG4)-related disease is a systemic fibro-inflammatory disease, which can affect the salivary glands in more than 30–40% of patients, submandibular glands more often than parotid glands, and bilateral salivary glands more often than unilateral salivary gland [ 58 ]. Other than salivary gland lesions, the most commonly involved organ is reportedly the lacrimal gland [ 59 ] ( Figure 5 ).…”
Section: Clinical Applications Of 3d Tse Pcasl In the Head And Neckmentioning
confidence: 99%
“…It has been used to help differentiate between the diseased and normal tissues in the liver, breast, thyroid, and prostate glands 17–20 . For the major salivary gland, high‐resolution ultrasound is a useful and effective assessment tool due to the superficial location without invasion or radiation exposure 21 . In patients with primary Sjogren syndrome, the ultrasound characteristics in major salivary glands include more hypoechogeneity and inhomogeneity of the parenchyma with more unclear borders, hypoechoic areas, and hyperechogenic reflections than those of non‐Sjogren syndrome 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Sialolithiasis, as the most common reason (60-85 percent) 1 of obstructive salivary gland disease, in the rare cases, may be complicated by soft tissues abscess 2,3 or/and fistula. 4,5 A clinical study by Kishore Kumar et al (2012 ) of the 200 cases of cutaneous sinuses revealed that only in 0.5 percent of cases was noted cutaneous fistula as a result of submandibular gland calculus.…”
Section: Introductionmentioning
confidence: 99%